Identifikasi kromosom hasil cangkok anakan salak Sidempuan (Salacca sumatrana Becc.) di Kecamatan Angkola Barat - Friska, Meiliana (Jurnal Online Pertanian Tropik, 2019)
Salak Sidimpuan (Salacca sumatrana Becc.) is one of the superior commodities in South Tapanuli Regency. The availability of good quality zalacca varieties, high productivity, resistance to pests and diseases and tolerance to environmental stress are conditions that must be met in the era of agricultural industrialization. For this reason, it is necessary to assemble new superior salacca cultivars to meet the evolving demands of consumers and to anticipate potential cultivation constraints. Zalacca chromosome analysis is expected to be able to produce information about the chromosome composition of these plants, which can then be useful in supporting zalacca breeding. The aim of this study was to obtain the identity of the Salacca Sumatrana Becc. The plant-based on the morphological characteristics of chromosomes (number, shape, and karyotype of chromosomes). This research was conducted at the Laboratory of Genetics, Faculty of Biology, University of North Sumatra, Medan in April-May 2019. The results of this study indicate that Salak Sidempuan (Salacca sumatrana Becc.) have the number of chromosomes is 2n = 28, the shape of the chromosome and the karyotype formula was 2n = 9m + 5 sm (9 metacentric chromosomes and 5 submetacentric chromosomes)